Analysis of seabream and seabass consumption in the Mediterranean countries of the European Union - Luna Sotorrío L.; Fernández-Polanco J.M.; Fernández Sánchez J.L. (The Mediterranean fisheries sector. A reference publication for the VII meeting of Ministers of agriculture and fisheries of CIHEAM member countries (Zaragoza, Spain, 4 february 2008), 2008)
The overall objective of this study is to analyse the situation of the seabream and seabass market, in order to provide relevant information for designing sustainable development strategies. It is divided into two parts: the first is an aggregated study about the factors affecting consumption in the Mediterranean countries of the European Union, which concentrated 79.5% of the consumption of these species in 2005. The second part is more specific and studies the influence that awareness and attitude towards aquaculture has on consumption patterns and valuation of the species, factors that are to be taken into account when designing specific strategies for each market. This latter part is confined to the Spanish market, and therefore results cannot be extrapolated to others, but they may serve as reference given that Spain accounts for 18.6% of total seabream and seabass consumption in the European Union.
7. Meeting of Ministers of Agriculture and Fisheries of CIHEAM Member Countries, 2008/02/04, Zaragoza (Spain)